Explorers & scientists in China's borderlands, 1880-1950 - Glover, Denise Marie (University of Washington Press, 2011)
"The scientists and explorers profiled in this engaging study of pioneering Euro-American exploration of late imperial and Republican China range from botanists to ethnographers to missionaries. Although a diverse lot, all believed in objective, progressive, and universally valid science; a close association between scientific and humanistic knowledge; a lack of conflict between science and faith; and the union of the natural world and the world of "nature people." Explorers and Scientists in China's Borderlands examines their cultural and personal assumptions while emphasizing their remarkable lives, and considers their contributions to a body of knowledge that has important contemporary significance.Essays are devoted to D. C. Graham, Joseph Rock, Reginald Farrer and George Forrest, Ernest Henry Wilson, Paul Vial, Johan Gunnar Andersson and Ding Wenjiang, and Friedrich Weiss and Hedwig Weiss-Sonnenburg. Richly illustrated with historic photographs, this collection reveals the extraordinary lives and times of these remarkable people. Denise M. Glover is visiting assistant professor of anthropology, University of Puget Sound; Stevan Harrell is professor of anthropology, University of Washington; Charles F. McKhann is professor of anthropology, Whitman College; Margaret Byrne Swain is associate adjunct professor of women and gender studies, University of California, Davis. The other contributors are Magnus Fiskesjo, Paul Harris, He Jiangyu, Geng Jing, Jeff Kyong-McClain, Erk Mueggler, Alan Waxman, Paul Weissich, Tamara Wyss, and Alvin Yoshinaga"--Provided by publisher.